COMPARATIVE ANALYSIS OF THE NON-PERFORMING FINANCING SETTLEMENT IN ISLAMIC FINANCIAL INSTITUTIONS - Aulia, Fena Ulfa; Ulfah, Almira Keumala; Ismail, Sherif Mohamed; Hotman, Hotman (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
LKS has different characteristics, so different strategies and approaches are needed in resolving problematic financing. The purpose of the study is to analyze and compare strategies and approaches used in overcoming NPF in BPRS, BUS, and BMT. This research is a literature review with a qualitative approach using secondary data in the form of previous research results and as many as 12 research objects with documentation techniques. Data analysis techniques are carried out using data reduction, data analysis, and conclusions. This research shows that in general, the settlement of problematic financing is carried out by restructuring but by taking different approaches according to the character of BPRS, BUS, and BMT. In particular, there are some BMTs in solving NPFs that do not use approaches that correspond to their characteristics.